Knowledge and practice of postpartum care among mothers in Kuantan, Pahang - Salehudin, Saezah; Abdul Ghani, Radiah; A. Rahman, Nor Azlina (2015)
Postpartum care in the period after childbirth is very crucial not solely for survival but for the future of mothers and newborn babies. In Malaysia, there are several traditional postpartum care practices normally practiced by mothers and different states adopted different ways to perform those practices. However, the knowledge and benefits of those practices were still ill-defined. This study aims to identify knowledge and practice of postpartum care among mothers in Kuantan, Pahang. Moreover, this study aims to determine the association of socio-demographic data with confinement period, postpartum dietary practice and postpartum physical practice. The most significant factor that influences knowledge and practice of postpartum care among mothers in Kuantan also was determined. This is a cross-sectional study and 100 respondents were selected by using purposive sampling. The questionnaire forms were distributed among eligible respondents in Kuantan area which was at Tasik Bandar and through online survey. The questionnaire was divided into three categories which were personal details, practice of postpartum care and knowledge of postpartum care. The association of socio-demographic data with confinement period, postpartum dietary practice and postpartum physical practice were evaluated by using Chi-square test. There was no significant association of socio-demographic data which were age, level of education, occupation and number of children with confinement period (p>0.05). For postpartum dietary practice, there were only association between age and encourage more water intake (p=0.047, p<0.05) and also between number of children and prohibit greasy food (p=0.032, p<0.05). Apart from that, for association between socio-demographic data and postpartum physical practice, there was only association between age and body scrub (p=0.046, p<0.05). The most significant factor that influenced postpartum care practice was family tradition (83%). The major factor that contributed to knowledge of postpartum care was also family tradition (97 %). In conclusion, knowledge of postpartum care among mothers in Kuantan was good and the practice was prevalent among them.